The significance of non-motorised transport interventions : a case study of Greater Sekhukhune, Limpopo Province, South Africa - Rathete, Mmanake Maria (Department of Civil Engineering, 2016)
South Africa has a significant proportion of learners (64%) that use walking as a means of transport on a daily basis to a place of education, and workers (21.1%) to place of work ( Statistic SA, 2014), that are predominantly located in peri-urban and rural areas. Therefore, Non-Motorised Transport (NMT), should have greater priority in rural areas, but it is largely neglected, due to the lack of awareness of the role of NMT modes of transport, minimal funding and other basic transport infrastructural needs take preference over NMT. Non prioritisation of NMT among other reasons, results in high rates of pedestrian accidents, with approximately 40% of pedestrian fatalities recorded in South Africa (Arrive Alive, 2012). The primary purpose of the research is to address NMT road user safety by investigating and evaluating effective and appropriate measures that will address poor NMT facilities and infrastructure arrangement that meets the needs of NMT users in the study area of Greater Sekhukhune in Limpopo Province. To evaluate the Significance of NMT interventions, National and International literature, as well as primary and secondary data formed the basis of this study. The primary data was sourced by performing pedestrian surveys in the rural community of Sekhukhune.